Observasi Mental Model Penjumlahan Bilangan Bulat Siswa Sekolah Dasar Kota Baubau - Abdurahman Askois (Jurnal Akademik Pendidikan Matematika, 2021)
Skills on the integer system are the main competencies in developing learning in other, more complex number systems, but there are still many students who are not sufficiently proficient in these competencies. This study is an ethnographic study with the aim of describing the mental model and the nature of the consistency of integers that become the learning experience of students at elementary schools in Baubau City. This study provides information that the mental models of elementary school students in Baubau City found in integer learning are initial mental models, synthetic mental models and formal mental models. Students in working on integer addition operations still show inconsistencies when using number line media as a tool.